2005
DOI: 10.1113/jphysiol.2004.079509
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptor activity induces a novel oscillatory pattern in neonatal rat hypoglossal motoneurones

Abstract: Tongue muscles innervated by the hypoglossal nerves play a crucial role to ensure airway patency and milk suckling in the neonate. Using a slice preparation of the neonatal rat brain, we investigated the electrophysiological characteristics of hypoglossal motoneurones in the attempt to identify certain properties potentially capable of synchronizing motor commands to the tongue. Bath-applied DHPG, a selective agonist of group I metabotropic glutamate receptors (mGluRs), generated persistent, regular electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 80 publications
1
69
0
Order By: Relevance
“…For example, studies have shown that there is electrical coupling between hypoglossal motoneurons associated with breathing (Rekling et al 2000) and tongue movements (Sharifullina et al 2005) as well as among motoneurons in Xenopus embryos (Perrins and Roberts 1995). Furthermore, when gap junctions were blocked in Xenopus embryos, Zhang et al (2009) noted that the burst durations of motoneurons increased, resulting in alteration of rostro-caudal delays during fictive swimming.…”
mentioning
confidence: 99%
“…For example, studies have shown that there is electrical coupling between hypoglossal motoneurons associated with breathing (Rekling et al 2000) and tongue movements (Sharifullina et al 2005) as well as among motoneurons in Xenopus embryos (Perrins and Roberts 1995). Furthermore, when gap junctions were blocked in Xenopus embryos, Zhang et al (2009) noted that the burst durations of motoneurons increased, resulting in alteration of rostro-caudal delays during fictive swimming.…”
mentioning
confidence: 99%
“…Bursting is apparently paced by the cyclic activation of K ATP conductances, thus linking electrical discharges to the cell energy metabolism. Current clamp recording indicates that, during bursting, motoneuron spikes appear only at the peak of each burst, in contrast to the irregular firing emerging when the same cell is depolarized to a comparable level of membrane potential (Sharifullina et al 2005). Hence, bursts strongly constrain the firing pattern of motoneurons and amplify AMPA receptor-mediated synaptic inputs.…”
Section: Heterogeneity Of Motoneuron Rhythmic Bursting Evoked By Neurmentioning
confidence: 99%
“…To sum up, hypoglossal motoneurons can produce rhythmic bursting elicited by NMDA through a robust mechanism that is mainly intrinsic to these cells because it is unaffected by blockers of excitatory Bursts are observed as inward current (large downward deflections) with superimposed fast oscillations; for further details, see Sharifullina et al (2005Sharifullina et al ( , 2008. or inhibitory synaptic transmission (Sharifullina et al 2008), and that is preserved despite fluctuations in extracellular Mg 2þ .…”
Section: Heterogeneity Of Motoneuron Rhythmic Bursting Evoked By Neurmentioning
confidence: 99%
See 2 more Smart Citations